Women's Liberation: Swedish Feminist Comics and Cartoons from the 1970s and 1980s. Issue 2 (1st September 2019) - Nordenstam, Anna; Wallin Wictorin, Margareta
Abstract : In Sweden, publication of original feminist comics started in the 1970s and increased during the following decade. This article describes and analyses the Swedish feminist comics published in the Swedish radical journals Kvinnobulletinen and Vi Mänskor, as well as in the Fnitter anthologies. These comics, representing radical feminism, played an important role as forums for debate in a time when feminist comics were considered avant-garde. The most prominent themes were, first, the body, love and sexualities and, second, the labour market and legal rights. The most frequent visual style was a black contour line style on a white background, recalling the comics of Claire Bretécher, Aline Kominsky-Crumb and Franziska Becker. Humour and satire, including irony, were used as strategies to challenge the patriarchy and to contest the prevailing idea that women have no sense of humour.